The TanDEM-X Acquisition Timeline and Mission Plan - Fiedler, Hauke; Krieger, Gerhard; Zink, Manfred; Geyer, Michael; Jäger Jürgen, Jürgen (European Conference on Synthetic Aperture Radar (EUSAR), 2008)
This paper introduces the TanDEM-X data acquisition plan that fulfils the requirements of deriving a global DEM according to the emerging HRTI-3 quality standard within three years mission time. Therefore, a joint TerraSAR-X and TanDEM-X data acquisition concept is introduced. Taking this concept into account, a TanDEM-X data acquisition timeline is calculated. The performance with respect to height of ambiguity is optimised. By assuming a ground station network, mass memory states of both satellites are calculated to guarantee enough free space onboard both satellites for the TerraSAR-X mission. Finally, the TanDEM-X Mission Plan is presented.
DLR Import::2019-04-03